Bioremediation for Ochratoxin A by Using Some Species of Bacteria isolated from Iraqi Dates - A.Zaid, Basaid; K.Jabar, Haidar (Al-Qadisiyah Journal of Pure Science, 2018)
This study aimed to evaluate the effectiveness of some species of bacterial isolated from Iraqi Dates in the treatment of toxic Ochratoxin A and the possibility of appointment one isolate them as us drug country poison Ochratoxin A In Invivo. The study results showed the effectiveness of the bacteria Lactococcus plantrum in reducing the toxicity of Ochratoxin A externally (Invitro) since disappeared shine spot poison Ochratoxin A treatment with bacteria from the plate Thin layer chromatography when exposed UV , reinforced this result vital tests that took place inside the body of animals albino Rat and the transaction of Ochratoxin A pre- treatment bacterium Lactococcus plantrum that were in organ of the studied included the kidneys, completely intact while showed pathogenic changes clear in those animals treated with the organs of Ochratoxin A untreated bacteria. It also proved of the formula manufacturedfrom bacteria L. plantrum and debilitating heat highly effective in reducing the toxicity of Ochratoxin A demonstrated by the survival of all of the level of hemoglobin ,Keriatenin and urea the levels of these parameters were (14g/ml,23 g/dl and 65g/dl)respectively /, while the level s of above parameters in animals treated of Ochratoxin A only( 9g/ml,43g/dl and 320g/dl) respectively. On the other hand it was the preparation of vital important role in defense the tissues of animals treated by followed by treating them Ochratoxin A, as results showed histological examination of sections of textile for kidneys safety of any pathological changes , in the time it appeared pathological changes severe in all those organs of the animals organs tissues treated by Ochratoxin A only was the emergence of hypertrophy of glomerulus, necrosis and cells death of the tubules renal in kidneys.